ANALISIS PENERIMAAN RETRIBUSI PARKIR UNTUK PENINGKATAN PENDAPATAN ASLI DAERAH (STUDI KAJIAN PUBLIK DAN KEMASLAHATAN) - Afriana (LPPM Universitas Ekasakti, 2024)
Parking fees in Bireuen Regency are regulated by Qanun Number 10 of 2011 on Parking Service Fees on Public Roads. According to this Qanun, the target for parking fees from motor vehicles in the Kota Juang District of Bireuen Regency for 2022 was set at IDR 1,100,000,000. However, the actual revenue collected was only IDR 755,850,000, indicating a significant shortfall. This issue is attributed to the presence of illegal parking attendants whose revenues do not contribute to the regional budget. The aim of this study is to understand how the targets and actual revenue from parking fees fall short of the Qanun requirements. Utilizing analytical theory and a qualitative approach, the research examines activities and phenomena related to parking fee management to identify causes and appropriate solutions. The study concludes that the target and realization of the regional revenue from parking fees have not met the standards set by Qanun Number 10 of 2011.